Ford: how the model T revolutionised an industry - Baker, Michael J. (Henry Stewart Talks, 2018)
This case study considers Ford’s strategy in the early years of the 20th century and the development of the Model T which revolutionised the motor industry. This strategy was so successful—as a traditional demand curve would predict—because lowering the price of motor cars resulted in an increase in demand. This gave Ford two-thirds of the market share by 1916. However, through product differentiation and the development of a second-hand car market, General Motors outperformed Ford to gain market leadership.